2013
DOI: 10.1021/nl304734g
|View full text |Cite
|
Sign up to set email alerts
|

The Role of External Defects in Chemical Sensing of Graphene Field-Effect Transistors

Abstract: A fundamental understanding of chemical sensing mechanisms in graphene-based chemical field-effect transistors (chemFETs) is essential for the development of next generation chemical sensors. Here we explore the hidden sensing modalities responsible for tailoring the gas detection ability of pristine graphene sensors by exposing graphene chemFETs to electron donor and acceptor trace gas vapors. We uncover that the sensitivity (in terms of modulation in electrical conductivity) of pristine graphene chemFETs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 46 publications
5
111
0
Order By: Relevance
“…In the presence of DMMP, GB is additionally n-doped, as shown by a shifted transmission spectrum down (by B0.05 eV) with respect to E f , assuming that E f stays fixed with respect to the rest of the system (grains transmission spectra shown by green dashed lines). The 0.05 eV shift corresponds to an electron density concentration of B2.5 Â 10 11 cm À 2 , which is compatible with DMMP/graphene experimental values 23 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the presence of DMMP, GB is additionally n-doped, as shown by a shifted transmission spectrum down (by B0.05 eV) with respect to E f , assuming that E f stays fixed with respect to the rest of the system (grains transmission spectra shown by green dashed lines). The 0.05 eV shift corresponds to an electron density concentration of B2.5 Â 10 11 cm À 2 , which is compatible with DMMP/graphene experimental values 23 .…”
Section: Discussionsupporting
confidence: 87%
“…It was shown that the sensitivity of an isolated GB is B300 times higher than that of a single graphene grain and much larger than that of polycrystalline graphene sensors. We have verified that the presence of local transport gaps in GBs together with the local accumulation of gas molecules plays a crucial role in the observed large chemical sensitivity of GBs, so the mechanism differs from the previously reported carrier density modulation in carbon-based sensors 6,7,[23][24][25][26][27][28] . The sensing mechanism is based on a marked closing or opening of local conduction channels through the GB by the adsorbed …”
Section: Discussionmentioning
confidence: 49%
“…4, although all devices processed (including thermal oxide growth) in one batch show consistent behaviour. We attribute this to a substrate effect 32 where end terminations may preferentially orient the molecules through hydrogen bonding, but further detailed investigation is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Although defects may play a dominant role in the observed shifts, we can exclude that a unique defect or a contamination in our samples is responsible for the sensing mechanism by observing the same results on two different graphene samples from different sources. The SiO 2 substrate can also play an important role in the sensing mechanism of GFETs on SiO 2 as has been proposed recently 50 . Using DFT modelling it has been suggested that the sensitivity of graphene to gas adsorbates can be attributed to external defects in the insulating substrate 50 .…”
Section: Discussionmentioning
confidence: 99%